Good Teaching: Aligning Student and Administrator Perceptions and Expectations - Lazarus Nabaho; Joseph Oonyu; Jessica Norah Aguti (Laureate Education Inc, 2017)
Literature attests to limited systematic inquiry into students' conceptions of good teaching in higher education. Resultantly, there have been calls for engaging students in construing what makes good university teaching and in developing a richer conception of teaching excellence. This interpretivist study that is based on views of final year university students from six academic disciplines investigated students' conceptions of good teaching at Makerere University in Uganda. Students conceived good teaching as being student-centred, demonstrating strong subject and pedagogical knowledge, being approachable, being responsive, being organised, and being able to communicate well. Most of the conceptions of good teaching hinge  on what the teacher does (the means) rather than affording high quality student learning (an end). It can therefore been concluded that good teaching is a multi-dimensional construct that defies a single definition and cannot be assured and assessed using a single indicator.